Ten-year all-cause death after percutaneous or surgical revascularization in diabetic patients with complex coronary artery disease. (18th August 2021) - Wang, Rutao; Serruys, Patrick W; Gao, Chao; Hara, Hironori; Takahashi, Kuniaki; Ono, Masafumi; Kawashima, Hideyuki; O'leary, Neil; Holmes, David R; Witkowski, Adam; Curzen, Nick; Burzotta, Francesco; et al.
Abstract: Aims: The aim of this article was to compare rates of all-cause death at 10 years following coronary artery bypass grafting (CABG) or percutaneous coronary intervention (PCI) in patients with or without diabetes. Methods and results: The SYNTAXES study evaluated up to 10-year survival of 1800 patients with three-vessel disease (3VD) and/or left main coronary artery disease (LMCAD) randomized to receive either PCI or CABG in the SYNTAX trial. Ten-year all-cause death according to diabetic status and revascularization strategy was examined. In diabetics ( n = 452), the risk of mortality was numerically higher with PCI compared with CABG at 5 years [19.6% vs. 13.3%, hazard ratio (HR): 1.53, 95% confidence interval (CI): 0.96, 2.43, P = 0.075], with the opposite seen between 5 and 10 years (PCI vs. CABG: 20.8% vs. 24.4%, HR: 0.82, 95% CI: 0.52, 1.27, P = 0.366). Irrespective of diabetic status, there was no significant difference in all-cause death at 10 years between patients receiving PCI or CABG, the absolute treatment difference was 1.9% in diabetics (PCI vs. CABG: 36.4% vs. 34.5%, difference: 1.9%, 95% CI: −7.6%, 11.1%, P = 0.551). Among insulin-treated patients ( n = 182), all-cause death at 10 years was numerically higher with PCI (47.9% vs. 39.6%, difference: 8.2%, 95% CI: −6.5%, 22.5%, P = 0.227). Conclusions: The treatment effects of PCI vs. CABG on all-cause death at 10 years in patients with 3VD and/or LMCAD were similar irrespective of the presence of diabetes. There may, however, be a survival benefit with CABG in patients with insulin-treated diabetes. The association between revascularization strategy and very long-term ischaemic and safety outcomes for patients with diabetes needs further investigation in dedicated trials. Trial registration: SYNTAX: ClinicalTrials.gov reference: NCT00114972 and SYNTAX Extended Survival: ClinicalTrials.gov reference: NCT03417050. Graphical Abstract: